Case Report: Prenatal diagnosis of novel compound heterozygous variants in WDR35 gene causing short-rib thoracic dysplasia 7 with or without polydactyly - Zhuang, Jianlong; Wang, Junyu; Huang, Zhengping; Chen, Yu’e; Chen, Chunnuan (Frontiers in Pediatrics, 2025)
BackgroundWhole exome sequencing (WES) technology has been increasingly used for the etiological diagnosis of fetuses with ultrasound anomalies. In this article, we report a novel deletion compound combined with a causative variant in WDR35 gene leading to short-rib thoracic dysplasia 7 (SRTD7) with or without polydactyly using WES.MethodsThis study involved a Chinese fetus with clinical features of skeletal dysplasia on ultrasound imaging, in whom chromosome abnormalities and copy number variants (CNVs) were detected by chromosomal microarray analysis (CMA), and sequence variants were detected by WES. The obtained results were further verified by Sanger sequencing or real time quantitative PCR (qPCR).ResultsNo chromosomal abnormality or CNVs were identified in the fetus by CMA. However, WES result revealed a 14.38-kb large novel deletion compound covering exon 7 to exon 12 combined with a missense variant NM_001006657.2:c.932G>T(p.W311l) in WDR35. Both variants were thought of as pathogenic, which was further confirmed by Sanger sequencing and qPCR. In addition, two compound heterozygous variants NM_015102.5:c.[1196A>G(p.E399G)];[1972C>T(p.R658*)] in NPHP4 gene were also identified in the fetus, which may be partially responsible for fetal kidney hyperechogenicity and oligohydramnios.ConclusionThis is the first study reporting a novel deletion compound combined with a causative missense variant in WDR35 leading to SRTD7. This finding may broaden the spectrum of variants of WDR35 gene and provide a valuable reference for clinical counseling of related abnormalities in pregnancies.